A comparison of rate‐based and latency‐based assessments for determining demand aversiveness. (26th May 2020) - Liollio, Stephanie P.; Scheithauer, Mindy; Call, Nathan
Abstract : Demand assessments are used to determine the relative aversiveness of demands. This study compared two demand assessments (i.e., rate‐based and latency‐based) proposed in past research with three children with intellectual and developmental disabilities. We compared the hierarchical outcomes of demand aversiveness and efficiency of the two assessments. Differing degrees of correspondence between the assessments was found across participants. The latency‐based measure was most efficient for a participant with high‐rates of problem behavior. The rate‐based assessment was more efficient for a participant with low‐rates of problem behavior. More research is needed to determine when the different assessments should be conducted.